Anatomy dental during the COVID-19 - VALENZUELA RAMOS, MARISEL ROXANA (2020)
The objective of this study was to evaluate the teaching-learning of dental anatomy e-learning during the Covid-19 pandemic. A cross-sectional investigation was carried out. The teaching-learning of the students of dental anatomy. To do this, a questionnaire was developed that consisted of four dimensions that were, the methodologies used in teaching-learning, evaluations, coexistence and, the virtual classroom space, each of the dimensions mentioned had 5 questions with a total of 20 questions. The evaluation of the teaching-learning of dental anatomy e-learning during the Covid-19 pandemic varied among the participants, when performing the analysis of the four dimensions, the majority of positive responses were in the evaluation dimension, followed by the methodologies dimension of teaching, coexistence in the virtual classroom and virtual classroom. Also, the frequencies of the responses were higher in the evaluations from good and very good, these frequencies being significant (Table 2, p-value <0.01). A statistically significant difference between men and women was found between positive and negative ratings (Table 3, p-value <0.01). The students had more positive than negative responses, the dimension that obtained the highest percentage of positive responses was the evaluation dimension. In general, students evaluate the teaching-learning evaluation of dental anatomy e-learning during the Covid-19 pandemic as very good, showing itself in all dimensions.